E-administration and employee service delivery in selected government ministries in Anambra state: 2015-2023 - Okeke, Mary Ngozi; Anaekwe, Victor Benjamine (PT. Pena Produktif Kreatif, 2025)
The rapid advancement of digital technologies has transformed public administration worldwide, making e-administration a critical tool for enhancing government service delivery. The study used a survey research design with structured questionnaires to collect data from 294 respondents across four ministries in Anambra State, Nigeria, representing a population of 1,105 employees. Proportionate sampling ensured fair representation from Education (112), Finance (114), Works (38), and Women Affairs (30) ministries. Data was analyzed using SPSS, employing frequency tables, percentages, and independent samples t-tests. The questionnaire was validated by academic experts and pre-tested for reliability, achieving strong internal consistency. The result showed that females constituted 65.6% and males 34.4%. Most respondents (56.5%) had under 15 years of experience. Regarding e-administration's impact on service delivery, 53.1% strongly disagreed that it improved workflows, and 43.9% disagreed that collaboration increased service delivery. However, 43.9% strongly agreed that automation improved service delivery, and 56.5% strongly agreed training was key. Most (90.5%) disagreed with improved digital communication boosted efficiency. Statistical tests showed no significant difference in service delivery scores between employees with less than 15 years (mean=30.48) and over 15 years (mean=29.95) experience (p > 0.05), rejecting the hypothesis that experience affects e-administration impact. The results underscore the need for improved ICT infrastructure, targeted training programs, and stronger organizational support to optimize the benefits of digital governance. The study concludes that although e-administration holds substantial potential for improving service delivery in public institutions, its success depends on strategic implementation, continuous staff development, and sustained institutional commitment.